Lipid and Carbohydrate Metabolism in Caenorhabditis elegans - Watts, Jennifer L; Ristow, Michael (Genetics (Austin), 2017)
Lipid and carbohydrate metabolism are highly conserved processes that affect nearly all aspects of organismal biology. eat bacteria, which consist of lipids, carbohydrates, and proteins that are broken down during digestion into fatty acids, simple sugars, and amino acid precursors. With these nutrients, synthesizes a wide range of metabolites that are required for development and behavior. In this review, we outline lipid and carbohydrate structures as well as biosynthesis and breakdown pathways that have been characterized in We bring attention to functional studies using mutant strains that reveal physiological roles for specific lipids and carbohydrates during development, aging, and adaptation to changing environmental conditions.